OATP1A2 mediates Aβ1-42 transport and may be a novel target for the treatment of Alzheimer’s disease - Wen, Jinhua; Zhao, Menghua; Xiao, Yuwei; Li, Sihong; Hu, Weiqiang (Frontiers in Pharmacology, 2024)
Alzheimer's disease (AD) is a neurodegenerative disease with an unknown cause. Many studies have suggested that the imbalance between the clearance and accumulation of β-amyloid protein (Aβ) in the brain of AD patients is the main cause of AD development of AD. Meanwhile, drug transporters play a key role in the transport of drugs and endogenous substances in vivo as well as in the development of many diseases. Could they be related to the imbalance between Aβ clearance and accumulation? OATP1A2 is the most abundant subfamily of organic anion transporting polypeptides (OATPs) that transport amphipathic substrates. Its high bilateral expression in brain endothelial cells suggests it plays a crucial role in delivering drugs and neuroactive peptides to brain tissue. Could it also be involved in mediating the production and accumulation of Aβ in the central system? This could lead to an imbalance between Aβ clearance and accumulation, ultimately resulting in AD development. This hypothesis would be bold and novel in the field of science. In this study, we successfully established the OATP1A2-HEK293T transgenic cell model, and found that the uptake of Aβ1-42 by OATP1A2-HEK293T cells was significantly higher than that of NC-HEK293T control cells and human astrocytes by adding different concentrations of Aβ1-42 to the cells of each group, suggesting that OATP1A2 expressed in the human brain is involved in Aβ amyloid protein transport.